MODEL PENELITIAN TOKOH (Dalam Teori dan Aplikasi) - Mustaqim, Abdul (UIN Sunan Kalijaga Yogyakarta, 2014)
The author explores some ways and its importance to biographical study in the Qur’an and Hadith. The purpose of research on biographical studies is to achieve a comprehensive understanding of the thoughts, ideas, concepts, and theories of someone he examined. The considerations in conducting this kind of research, among others, for example, his/her controverciality, influence, popularity, uniqueness, the intensity on the field of study that would scrutinized, relevance and contributions of his/her thinking in the context of the present.